Analisis Sistem Akuntansi Penggajian Dalam Efektivitas Pengendalian Internal Pada PT. Citra Indah Abadi Jaya - Putri Oktavia, Redita; Priono, Hero (Jurnal Etnik: Ekonomi-Teknik, 2023)
In every company must have several employees to run the business that has been run. Company PT. Citra Indah Abadi Jaya has a total of 58 employees and pays salaries to each employee once a month to be exact on the 1st. The purpose of this study is to analyze and explain the payroll system on the effectiveness of internal control at PT. Citra Indah Jaya Abadi. This study uses a qualitative method. Data collection techniques were carried out through observation, interviews and documentation. Based on these results indicate that PT.Citra Indah Abadi Jaya supports the effectiveness of internal control because it shows accountability to the authorities. Regarding the payroll system, documents that must be prepared, accounting records and payroll procedures are in accordance with established procedures, but some are not in accordance with procedures. determined as in concurrent duties, segregation of duties, and no salary certificate.